MMI, SCADA and ALARM philosophy for disturbed state operating conditions in an electrical utility - Candy, Richard Brodrick Charles (My University, 1995)
Advances in digital computing technology make it possible to improve the design of the Man Machine Interface (MMI), SCADA and ALARM modules used in electrical utility control centres. to overcome the problem of control staff data overloading. A possible solution is proposed, based on-an explicit representation of a disturbed power system state in addition to quiescent conditions. The structure of modem SCADA, installations is analysed in terms of the computing power of full graphic workstations, the quantities of element data delivered to the control room and the capabilities of intelligent remote terminal units. This analysis indicates that existing designs for the presentation of SCADA data need to change to solve the data overloading-problem. The proposed philosophy moves the focus of attention from the element level up to the device level by grouping and dividing all elements into categories at the RTU and linking them to their parent device, Control staff are notified graphically on the one-line displays, next to the device in question, of the existence of abnormal elements by category. The element state details for the device are only displayed on demand, resulting in a 95% reduction of alarm text messages. Suggestions are made as to the software functions needed at tbe RTU and the workstation to assist with the display of system data. Lastly racommendations are offered to reduce maintenance by standardising and pre-ordering device element data.
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering. Johannesburg 1995.
Keywords: Alarm; Electric power systems--Control; Control rooms--South Africa; Human-machine systems